Examining the interactions of Galahad™ compound with viruses to develop a novel inactivated influenza A virus vaccine. Issue 7 (July 2022) - Barnard, Dale L.; Belnap, David M.; Azadi, Parastoo; Heiss, Christian; Snyder, D. Scott; Bock, Susan C.; Konowalchuk, Thomas W.
Abstract: Galahad™ is a proanthocyanidin complexed with polysaccharides that inactivates viruses and indicates potential for an innovative approach to making protective vaccines. The polysaccharide portion of Galahad™ consists mainly of arabinan and arabinogalactan. In a seven-day toxicity study in rats, it was not toxic even when tested undiluted. Galahad™ inactivated a wide range of DNA and RNA viruses including adenoviruses, corona viruses such as SARS-CoV-2, and influenza viruses. Electron microscopy studies showed that exposure to Galahad™ caused extensive clumping of virions followed by lack of detection of virions after longer periods of exposure. Based on the viral inactivation data, the hypotheses tested is that Galahad™ inactivation of virus can be used to formulate a protective inactivated virus vaccine. To evaluate this hypothesis, infectious influenza A virus (H5N1, Duck/MN/1525/81) with a titer of 10 5.7 CCID50 /0.1 ml was exposed for 10 min to Galahad™. This treatment caused the infectious virus titer to be reduced to below detectable limits. The Galahad™ -inactivated influenza preparation without adjuvant or preservative was given to BALB/c mice using a variety of routes of administration and dosing regimens. The most protective route of administration and dosing regimen was when mice were given the vaccine twice intranasally, the second dose coming 14 days after the primary vaccine dose. All the mice receiving this vaccine regimen survived the virus challenge while only 20% of the mice receiving placebo survived. This suggests that a Galahad™-inactivated influenza virus vaccine can elicit a protective immune response even without the use of an adjuvant. This technology should be investigated further for its potential to make effective human vaccines. Highlights: Discovery of novel virus-inactivating agent: polysaccharide/catechin (Galahad™). Non-toxic: inactivates/lowers titers in 25 viruses, including Avian H5N1, COVID-19. Agent used to make whole virus vaccine; tested in 400 animal mouse model. Galahad™-inactivated vaccine 100% successful intranasally vs. lethal H5N1 challenge. Platform offers possible benefits—in time, cost, & mass distribution. Abstract : Vaccine; Polysaccharide; Catechin; Influenza; H5N1; SARS-CoV-2 (COVID-19).